Encapsulation of Natural Bioactive Compounds by Electrospinning—Applications in Food Storage and Safety - Bogdănel Silvestru Munteanu (MDPI AG, 2021)
Packaging is used to protect foods from environmental influences and microbial contamination to maintain the quality and safety of commercial food products, to avoid their spoilage and to extend their shelf life. In this respect, bioactive packaging is developing to additionally provides antibacterial and antioxidant activity with the same goals i.e., extending the shelf life while ensuring safety of the food products. New solutions are designed using natural antimicrobial and antioxidant agents such as essential oils, some polysaccharides, natural inorganic nanoparticles (nanoclays, oxides, metals as silver) incorporated/encapsulated into appropriate carriers in order to be used in food packaging. Electrospinning/electrospraying are receiving attention as encapsulation methods due to their cost-effectiveness, versatility and scalability. The electrospun nanofibers and electro–sprayed nanoparticles can preserve the functionality and protect the encapsulated bioactive compounds (BC). In this review are summarized recent results regarding applications of nanostructured suitable materials containing essential oils for food safety.